Faktor yang mempengaruhi manajemen laba pada sektor perbankan Indonesia - Nurshadrina Kartika Sari; Diana Dwi Astuti (Journal of Business & Banking, 2015)
Banks are responsible for the financial service in order that they become an important role in the community. They provide credit loan facilities for industries, government, small and medium business Banks can get into trouble if their performance in the fi-nancial report is not matching with the actual earnings. They have to present the fi-nancial report, so that the management gets a higher bonus and the stakeholders are satisfied and finally they can invest more money. The research tries to acknowledge the factors that influence the earning management. These factors are business risk, owner-ship structure (management structure and institution structure), banking size, and CAR. This research uses the data from 31 banks in Indonesia in the period of 2008 until 2012 and analyses them using a multiple linier regression test with dummy va-riables. It was found that the factors of management ownership, institution ownership, banking size, and CAR influence the earning management of banks in Indonesia.